2024
DOI: 10.1038/s41598-024-52391-y
|View full text |Cite
|
Sign up to set email alerts
|

The temporal progression of retinal degeneration and early-stage idebenone treatment in the Pde6brd1/rd1 mouse model of retinal dystrophy

Lei Zhang,
Wei Liu,
Hai-Yan Wang
et al.

Abstract: Photoreceptor cell death, primarily through apoptosis, related to retinal disorders like retinitis pigmentosa (RP), would result in vision loss. The pathological processes and crucial mutant conditions preceding photoreceptor cell demise are not well understood. This study aims to conduct an in-depth examination of early-stage changes in the widely utilized Pde6brd1/rd1 (rd1) mouse model, which has Pde6b gene mutations representing autosomal recessive RP disorder. We investigated the morphology and ultrastruct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Though the precise mechanisms of degeneration still need to be elucidated, it has been shown that already by Postnatal Day 3 of rd1 retinas, the mitochondria in the inner segments are swollen with less inner membrane cristae, and this abnormal development continues, resulting in deformed mitochondria [ 105 ]. Existing evidence suggests the accumulation of ROS in these abnormal mitochondria.…”
Section: Defective Mitochondria and Altered Vdac Expression In Diseas...mentioning
confidence: 99%
“…Though the precise mechanisms of degeneration still need to be elucidated, it has been shown that already by Postnatal Day 3 of rd1 retinas, the mitochondria in the inner segments are swollen with less inner membrane cristae, and this abnormal development continues, resulting in deformed mitochondria [ 105 ]. Existing evidence suggests the accumulation of ROS in these abnormal mitochondria.…”
Section: Defective Mitochondria and Altered Vdac Expression In Diseas...mentioning
confidence: 99%